Rancang Bangun Welding Fixture Table Untuk Pemotongan Dan Pegelasan Plat - Yuli Yetri; Oktavianus Ganumba; Ahmad Amdi Zamrud Kurnia; Daddy Budiman; Junaidi Junaidi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Welding (Welding) is an activity of connecting metals by going through the metal's liquid phase before finally solidifying and creating a connection. Welding techniques are increasingly widely used in building construction and machine construction. In addition to connecting metals, welding also has a function as a cutting medium. Welding and cutting is a job that requires accuracy. Welding work without tools will result in inaccurate results, so it requires an expert welder to get the desired results. The purpose of this research is to make a plate cutting tool called the Welding Fixture Table. This tool is used to help hold the workpiece in the form of a plate so that the cutting process is easy. This tool has the ability to clamp a maximum plate with a thickness of 6 mm of 750 mm x 610 mm with a weight of 21.6 Kg and can be adjusted to a smaller size, equipped with a sliding shift system on the table top to adjust the size of the workpiece clamping, as well as a system rotation which will make it easier for the operator to select the desired welding or cutting position.